The How Good Corporate Governance Influences Patient Satisfaction in Hospitals: A PRISMA-Based Systematic Review of Empirical Evidence - Wiyarti, Windi; Sepriany Putri Ali, Indri; Syukra Alhamda; Andi Indahwaty Sidin (CV. Get Press Indonesia, 2026)
Good Corporate Governance (GCG) has increasingly been recognized as a key governance mechanism in healthcare organizations, particularly in developing health systems. Purpose: This study aims to synthesize empirical evidence on the relationship between GCG implementation and patient satisfaction and to identify dominant governance mechanisms influencing patient-centered outcomes. Methods: A systematic literature review was conducted following the PRISMA framework. Ten peer-reviewed empirical studies published between 2019 and 2025 were included, the majority of which employed quantitative cross-sectional designs and were conducted in Indonesian hospital settings. Study quality and potential risk of bias were assessed narratively based on methodological rigor and measurement consistency. Results: The synthesis reveals a consistent positive association between GCG implementation and patient satisfaction, with transparency and accountability emerging as the most influential principles. These principles primarily affect patient satisfaction through trust-building, service quality enhancement, and operational efficiency, while the effects of fairness and responsibility appear more context-dependent. This review extends governance theory in healthcare by conceptualizing GCG not merely as an administrative control framework but as a relational mechanism that shapes patient experience through trust and service responsiveness. Implications: The findings highlight the need for hospital governance models that prioritize transparent information systems, accountable performance mechanisms, and patient-centered service processes to improve satisfaction outcomes.